The concession for forest resources exploration on the ancestral land under human rights perspective / Iwan Erar Joesoef - Joesoef, Iwan Erar (2021)
This paper investigates the granting of the concession for the exploration of natural resources on the ancestral forest. The research covers the regulation concerning the concession for exploration of the forest resources in Indonesia. This research uses document study as non-survey data collection such as regulations, the data of ancestral land conflict cited from related journals, and the court decision. This paper's contribution is to give the legal analysis of the Constitution Supreme Court decision that is to redefine the term of ancestral forest as not to be controlled by the state. The result on the granting of the concession for exploration of the forest resources was against the Indonesian constitution and human rights of Pancasila. It has led to the arise of many legal conflicts between the holder of concession and the Indigenous Law Community from which Government should be allowed to be good governance. Government should comply to the principles of Good Governance in all their decisions including the granting of the concession, of which is based on written and unwritten law